Topographic Habitat Drive the Change of Soil Fungal Community and Vegetation Soil Characteristics in the Rhizosphere of Kengyilia thoroldiana in the Sanjiangyuan Region - Liangyu Lyu; Pei Gao; Zongcheng Cai; Fayi Li; Jianjun Shi (Journal of Fungi)
This study aims to reveal the impact mechanisms of five typical topographic habitats in the Sanjiangyuan region (sunny slope, depression, shady slope, mountain pass, and transitional zone) on the characteristics and functions of rhizosphere soil fungal communities of Kengyilia thoroldiana, and to elucidate the association patterns between these communities and soil physicochemical factors. The species composition, diversity, molecular co-occurrence network, and FUNGuild function of microbial communities were investigated based on high-throughput sequencing technology. By combining the Mantel test and RDA analysis, the key habitat factors affecting the structure of the soil fungal community in the rhizosphere zone of Kengyilia thoroldiana were explored. The results showed that: ① The composition of the soil fungal community in the rhizosphere of Kengyilia thoroldiana in five topographical habitats showed significant differentiation characteristics: the number of OTUs in H2 (depression) and H5 (transitional zone) habitats was the highest (336 and 326, respectively). Habitats H2 showed a significant increase in the abundance of Ascomycota and Mortierellomycota and a significant decrease in the abundance of Basidiomycota compared to the other topographical habitats. ② The diversity and aggregation degree of the soil fungal community in the rhizosphere of Kengyilia thoroldiana in five topographical habitats showed differences. ③ Cluster analysis showed that the rhizosphere soil fungi in five topographical habitats of Kengyilia thoroldiana could be divided into two groups, with H2, H4 (mountain pass), and H5 habitats as one group (group 1) and H1 and H3 (shady slope) as one group (group 2). ④ The characteristics of the Kengyilia thoroldiana community and the physical and chemical properties of rhizosphere soil in five topographical habitats were significantly different, and the height, coverage, biomass, and soil nutrient content were the highest in H2 and H5 habitats, while lower in H1 and H3 habitats, with significant differences (p < 0.05). ⑤ Redundancy analysis showed that soil water content was the main driving factor to change the structure and function of the soil fungal community in the rhizosphere of Kengyilia thoroldiana in five topographic habitats in the Sanjiangyuan region. This study demonstrated that topographic habitats affected the species composition, functional pattern, and ecosystem service efficiency of the Kengyilia thoroldiana rhizosphere fungal community by mediating soil environmental heterogeneity, which provides microbial mechanistic insights for alpine meadow ecosystem protection.